THU0250 EARLY IMPROVEMENT IN SLEDAI-2K RESPONDER INDEX-50 PREDICTS SRI-4 RESPONSE IN A RANDOMIZED PLACEBO-CONTROLLED TRIAL OF USTEKINUMAB (UST) IN SYSTEMIC LUPUS ERYTHEMATOSUS. (June 2019) - Touma, Zahi; Gladman, Dafna D; Rose, Shawn; Fei, Kaiyin; Irene Gregan, Y; Gordon, Robert; Lo, Kim Hung; Urowitz, Murray B
Abstract : Background: While traditional Systemic Lupus Erythematosus (SLE) Disease Activity Index 2000 (SLEDAI-2K) scoring assesses complete SLE response for individual disease manifestations, the SLEDAI-2K Responder Index-50 (S2K RI-50) evaluates responses using partial improvement (≥50%) in each of the 9 organ systems of SLEDAI-2K. Ustekinumab (UST), a monoclonal antibody that targets the shared p40 subunit of the cytokines IL-12 & IL-23, is being investigated in patients with active SLE. We have previously shown in a Phase 2 placebo (PBO)-controlled trial of UST in SLE 1 that not only SLEDAI-2K and the SLE Responder Index 4 (SRI-4), but also S2K RI-50 can discriminate a treatment effect of UST vs PBO at week 24. 2, 3 Objectives: Here, we aimed to ascertain whether a minimal threshold of partial improvement in S2K RI-50 could be used as an early predictor of SRI-4 response. Methods: This phase 2, PBO-controlled study enrolled adults with seropositive, active disease (SLEDAI score ≥6 with ≥1 BILAG A &/or ≥2 BILAG B scores) despite standard therapy. Patients (n=102) were randomized (3:2) to receive UST IV ∼6 mg/kg or PBO at week 0, followed by SC injections of UST 90mg or PBO q8w beginning at week8, both added to standard of care. We calculated S2K RI-50 response through week 24 in all patients, including 60 patients receiving UST and 42 patients receiving PBO, using increasing cut-offs of S2K RI-50 reductions from baseline. To help determining a minimal cut-off that discriminated a treatment effect reflecting partial improvement, nominal p values are reported for this post hoc analysis. Logistic regression models were used to evaluate the relationship between reduction in S2K RI-50 at week 12 or week 16 and SRI-4 response at week 24, followed by correlation of binary response data between the two instruments. Results: A 2-point reduction from baseline (improvement) in S2K RI-50 appeared to be the lowest threshold of response to demonstrate a treatment difference in the proportion of responders at week 24 with UST (93.5%) vs PBO (79.3%) (Δ14.2%, p=0.03). The relationship between 2-point improvement in S2K RI-50 at week 12 or week 16 and SRI-4 response at week 24 is presented in the total study population and by treatment group (Table). In the total population, 78/102 (76.6%) patients at week 12 and 74/102 (72.5%) of patients at week 16 had at least a 2-point improvement in S2K RI-50. Of those, 47/78 (60.3%, r=0.62) at week 12 and 48/74 (64.9%, r=0.76) at week 16 achieved an SRI-4 response at week 24. Odds ratios for the association between SRI-4 response at week 24 and 2-point or greater improvement in S2K RI-50 were 7.6 (CI 2.4-24.3, p=0.0007) at week 12 and 15.4 (CI 4.2-55.8, p<0.0001) at week 16. Similar analyses performed by treatment group demonstrated that these relationships were consistent in the UST and PBO groups (Table). Conclusion: 2K RI-50 captures partial improvement of ≥50% in SLE disease activity and could be a useful outcome in clinical trials to predict early clinical response. These findings will be confirmed in an ongoing Phase 3 study. References: [1] van Vollenhoven, et al. Lancet. 2018:392:1330. [2] Touma Z, et al. EULARJune2018, Amsterdam, NL. [3] Touma Z, et al. APLAR. April2019, Brisbane, Australia. Disclosure of Interests: Zahi Touma Grant/research support from: GSK Canada, Consultant for: UBC, Pfizer, Janssen, Inc, Dafna D Gladman Grant/research support from: AbbVie, Amgen, Celgene, Lilly, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Amgen, BMS, Celgene, Galapagos, Gilead, Janssen, Lilly, Novartis, Pfizer, and UCB, Shawn Rose Employee of: Janssen Research & Development, LLC, Kaiyin Fei Employee of: Janssen Research & Development, LLC, Y Irene Gregan Employee of: Janssen Research & Development, LLC, Robert Gordon Employee of: Janssen Research & Development, LLC, Kim Hung Lo Employee of: Janssen Research & Development, LLC, Murray B Urowitz Grant/research support from: GSK, Consultant for: BMS, Celgene, GSK, Lilly, UCB